2018
DOI: 10.12659/msm.906507
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression and Clinical Value of hsa_circ_0049224 and has_circ_0049220 in Systemic Lupus Erythematous Patients

Abstract: BackgroundThe aim of this study was to discuss the possible roles and clinical value of 2 circRNAs (hsa_circ_0049224 and has_circ_0049220) in SLE patients.Material/MethodsReverse-transcription real-time polymerase chain reaction (RT-PCR) was conducted to detect the expressions of hsa_circ_0049224, has_circ_0049220, and DNMT1 in peripheral blood mononuclear cells (PBMCs) from 18 diagnosed SLE patients and 10 healthy controls.ResultsWe found that the expressions of hsa_circ_0049224 and has_circ_0049220 in health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…For instance, AKT could coordinate IL-2 signaling and T-cell antigen receptor to hold the expression of adhesion molecules, cytolytic effector molecules, as well as cytokine and chemokine receptors in cytotoxic T cells 76 . Another research showed that hsa_circ_0049224 and has_circ_0049220 were underexpressed in PBMCs of inactive and active SLE patients 77 . Moreover, the levels of these two circRNAs were negatively correlated with SLEDAI and the degree of SLE severity, which indicated that they might be regarded as markers for the activity and severity of SLE.…”
Section: Circrnas In Autoimmune Diseasesmentioning
confidence: 99%
“…For instance, AKT could coordinate IL-2 signaling and T-cell antigen receptor to hold the expression of adhesion molecules, cytolytic effector molecules, as well as cytokine and chemokine receptors in cytotoxic T cells 76 . Another research showed that hsa_circ_0049224 and has_circ_0049220 were underexpressed in PBMCs of inactive and active SLE patients 77 . Moreover, the levels of these two circRNAs were negatively correlated with SLEDAI and the degree of SLE severity, which indicated that they might be regarded as markers for the activity and severity of SLE.…”
Section: Circrnas In Autoimmune Diseasesmentioning
confidence: 99%
“…Zhang et al initially focused on 2 circRNAs (hsa_circ_0049224 and hsa_circ_0049220), which have been demonstrated to be correlated with DNA methylation and the pathological processes of rheumatoid arthritis (RA) ( 100 ). Subsequently, they found that expression levels of hsa_circ_0049224 and hsa_circ_0049220 were significantly decreased in PBMCs of SLE patients and were negatively correlated with SLE disease activity index (SLEDAI) score ( 91 ). Moreover, the expression levels of these two circRNAs were positively correlated with the expression of DNMT1, a key factor of DNA methylation, which suggests their possible roles in the pathogenesis of SLE.…”
Section: Circrnas In Slementioning
confidence: 99%
“…The circRNAs studied, circ_0049224 and circ_0049220, target DNA methyltransferase 1 (DNMT1), and DNA hypomethylation has been correlated with SLE [ 59 ]. The results showed that the expression level of DNMT1 was positively linked to the expression of the two circRNAs and that these two circRNAs were downregulated in SLE patients [ 103 ]. Moreover, there was a negative correlation between the SLE activity and the expressions of circ_0049224 and circ_0049220 [ 103 ].…”
Section: Role Of Ncrnas In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…The results showed that the expression level of DNMT1 was positively linked to the expression of the two circRNAs and that these two circRNAs were downregulated in SLE patients [ 103 ]. Moreover, there was a negative correlation between the SLE activity and the expressions of circ_0049224 and circ_0049220 [ 103 ].…”
Section: Role Of Ncrnas In Systemic Lupus Erythematosusmentioning
confidence: 99%